Influence of Vitamin D Level on Inflammatory and Prognostic Markers in COVID-19 - A Retrospective Study - Singh, Sunil K.; Singh, Shruti; Kumar, Rajesh; Rana, Proteesh; Sharma, Ajay; Karwasra, Ritu; Kesharwani, Prashant; Sahebkar, Amirhossein (Recent Advances in Food Nutrition & Agriculture, 2023)
Objective: The ongoing pandemic of severe acute respiratory syndrome coronavirus 2019 (SARS-CoV-2) has caused an immense public health crisis worldwide. Emerging evidence has suggested that inflammatory response plays a critical role in the pathogenesis and prognosis of the disease. As vitamin D can modulate the immune system, this study has been designed to correlate vitamin D with inflammatory and prognostic markers in COVID-19 patients.Methods: The present study is a retrospective study examining the relationship between vitamin D levels and inflammatory markers in the COVID-19 disease. COVID-19 patients who were investigated for vitamin D, ferritin, D-dimer, C-reactive protein (CRP), and procalcitonin (PCT) level were only included. The patients were divided into hypovitaminosis D, and normal vitamin D. Correlation and logistic regression analyses were carried out to identify the strength and association of hypovitaminosis D with inflammatory markers in COVID-19 disease.Results: The hypovitaminosis D group had significantly higher inflammatory markers compared to the normal vitamin D group. The correlation between hypovitaminosis D and procalcitonin was negative (r = -0.433), with a strong and significant association (p = 0.002). The correlation between hypovitaminosis D, CRP, and ferritin was weak and insignificant. The logistic regression between hypovitaminosis D and procalcitonin established a significant regression equation, leading to a significant linear model.Conclusion: This study concludes that patients with hypovitaminosis D should be treated with vitamin D therapy to reduce the severity of COVID-19 disease.
Keywords: vitamin D